PERANAN TENTARA PELAJAR DALAM PERANG EMPAT HARI DI SOLO PADA TAHUN 1949. - Rizki Tirnando; Ridwan Melay; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstracts: Army Student is a young youth, middle school students (JUNIOR HIGH SCHOOL), a secondary school (HIGH SCHOOL) and also students who rose up independence along with the people. The soldiers of this average Student age of 15-20 years, but her spirit is not lost by Indonesia's army to maintain its independence, they are aware that energy and enthusiasm required by Indonesia. It is proven by the army in the student participated directly in a war on the first Dutch military aggression in Indonesia. As for the purpose of this research is to know the background of the establishment of the Student Army. To find out how the condition of the Student Army before the war four days in Solo in 1949. To examine the role of Student Soldiers in war four days in Solo in 1949. To find out how a student Army Role after the end of the war four days in Solo in 1949. The method used in this research is qualitative and historical methods. The data collected through the techniques of librarianship and documentation. Data obtained from books, magazines, and articles on its own analysis. Then in analyzing using deskriftif qualitative. The result of this research was a student Soldier of the time calculated is still young, but his spirit was still high to maintain the State of Indonesia from the Netherlands military aggression action, they willingly left the school bleachers for the sake of maintaining Indonesia, the army students engage directly with some of the war that ensued, one of the largest Student Army war against the Netherlands namely War four days in Solo in order to improve the bargaining position of Indonesia against the round table Conference agreements conducted in Den Haag Netherlands.Keywords: Student, Army War four days in Solo.